Educational Curriculum Concept; Interpretation for Teachers in Designing Learning and Achieving Goals - Arsyad; Safitriani (Yayasan pendidikan dzurriyatul Quran, 2023)
Education is an inseparable part of today's life, even in this era of globalization, the level of education influences both individual and national competitiveness internationally. Therefore, one of the important instruments in supporting the learning process so that it is integrated and evenly distributed is by implementing the same curriculum. The aim of this research is to analyze and describe the concept of educational curriculum. This research method is library research. Data collection is carried out by searching or examining several books, journals and documents in both printed and electronic formats, as well as information or other data sources that are relevant to the study or research. The results of this research can be explained that the concept of curriculum develops along with the development of educational theory and practice. Curriculum in education is the core of education and characterizes schools as institutions operating in the field of educational services. The curriculum concept consists of 5 concepts, namely; (a) Concept of academic subject curriculum, (b) Concept of cognitive development process curriculum, (c) Concept of curriculum reconstruction, (d) Concept of humanistic curriculum, (e) Concept of technology curriculum